Effects of an online mindfulness-based program for parents of children with attention deficit/hyperactivity disorder: a pilot, mixed methods study - Lo, Herman Hay Ming; Lam, Jason; Zhang, Zoe Ji-wen; Cheung, Marsena; Chan, Stanley Kam Chung; Wong, Elisabeth Wai Yin; Bögels, Susan M.; Chui, Wing Hong (Frontiers in Psychiatry, 2024)
Objectives Online mindfulness-based program (MBP) for parents and families especially in clinical population is limited. Engagement and significant dropout are major issues in MBP implementation. This pilot study examined the effects of an online mindfulness-based program (MBP) on parents of children with Attention Deficit/Hyperactivity Disorder (ADHD). Methods A mixed methods study was applied to evaluate the effects of the MBP. A total of 43 parents were recruited and were randomly assigned into intervention group and waitlist control group. The online MBP lasted for 28 days, including 20 psychoeducation videos, homework audio guidance, and four instructor-led online group meetings. Purposive sampling was used to recruit parents who completed the program to share their experiences and suggestions for improving the program in semi-structured online interviews. Results Quantitative data showed that participants from the online MBP reported a medium to large effect on the reduction of child ADHD symptoms. In semi-structured interviews, participants reported positive experiences in their help seeking intention, and personal changes, such as emotion regulation and quality attention to their children. Participants further made suggestions for improvement. Conclusions The effect of online MBP is promising, and the program should be conducted. A large scale randomized controlled trial should be conducted to investigate the effects of MBP in clinical populations. Clinical trial registration ClinicalTrials.gov NCT05480423.